PENGEMBANGAN SISTEM REPOSITORI SKRIPSI DI TEKNIK INFORMATIKA UNIVERSITAS NEGERI MANADO BERBASIS WEB - Chrysilia Rimbing; Gladly Rorimpandey; Vivi Rantung (JOINTER : Journal of Informatics Engineering, 2023)
Based on observations made by researchers at Informatics Engineering Universitas Negeri Manado, there is no Thesis Repository that functions to accommodate data on Thesis Titles of Informatics Engineering Study Program Students. Based on this, researchers plan to develop a web-based Thesis Repository System at Universitas Negeri Manado Informatics using the Agile Software Development method. After the web-based Thesis Repository System in Informatics Engineering Universitas Negeri Manado was successfully developed using the Agile Software Development method, testing carried out using the black box testing method obtained good results, where 12 test points were successfully achieved and the developed system could help the study program in recording thesis data from students.